2022
DOI: 10.3389/fpls.2022.980171
|View full text |Cite
|
Sign up to set email alerts
|

Drought resistance of tobacco overexpressing the AfNAC1 gene of Amorpha fruticosa Linn.

Abstract: Plants are often adversely affected by abiotic stresses such as drought, low temperature, and salinity during growth, and plant NAC-like transcription factors are involved in regulating growth and developmental processes in response to stresses such as drought and salinity. In this study, to investigate the function of AfNAC1, a co-expression network of AfNAC1 genes was constructed using gene expression data from the Chinese legume deciduous shrub, Amorpha fruticosa Linn. A 576 bp NAC transcription factor (AfN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Results showed that all traits were influenced by accessions, a key that may also demonstrate genetic content that probably influences variation. Furthermore, studies have been conducted on the expression of genes associated with drought [25], phenolic constituents [26], proteomic analysis of symbiotic proteins [27], and cancer research [28,29]. The aforementioned research signifies from one point of view the significance of A. fruticosa, although we cannot eliminate the negative effects that it has on ecosystems due to its rapid expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that all traits were influenced by accessions, a key that may also demonstrate genetic content that probably influences variation. Furthermore, studies have been conducted on the expression of genes associated with drought [25], phenolic constituents [26], proteomic analysis of symbiotic proteins [27], and cancer research [28,29]. The aforementioned research signifies from one point of view the significance of A. fruticosa, although we cannot eliminate the negative effects that it has on ecosystems due to its rapid expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also observed for HuNAC20 and HuNAC25 , two novel NAC genes from pitaya ( Hu et al, 2022 ). AfNAC1 from Amorpha fruticosa may have a part in photosystem regulation and indirectly confer plant resistance to drought stress ( Li et al, 2022 ). By contrast, TaSNAC4-3D negatively regulated drought tolerance by bringing about increased oxidative damage and programmed cell death in wheat ( Ma et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%